2019
DOI: 10.1128/jvi.00608-19
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Leukemia Virus Type 1 (HTLV-1) bZIP Factor Upregulates the Expression of ICAM-1 To Facilitate HTLV-1 Infection

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) causes multiple pathological effects, ranging from a form of leukemia to a spectrum of inflammation-mediated diseases. These diseases arise from one or several infected CD4+ T cells among thousands acquiring proliferation and survival advantages and ultimately becoming pathogenic. Given the low incidence of HTLV-1-associated diseases among carriers, such cellular evolutionary processes appear to occur rarely. Therefore, infectious spread of HTLV-1 within the T-cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…The viral protein HBZ was recently shown to enhance HTLV-1 infection by activating ICAM-1 expression [31]. HBZ regulates transcription of many other cellular genes as well as transcription of the HTLV-1 provirus [32].…”
Section: Introductionmentioning
confidence: 99%
“…The viral protein HBZ was recently shown to enhance HTLV-1 infection by activating ICAM-1 expression [31]. HBZ regulates transcription of many other cellular genes as well as transcription of the HTLV-1 provirus [32].…”
Section: Introductionmentioning
confidence: 99%
“…Tax regulates virus transmission by inducing and cooperating with intercellular adhesion molecule 1 (ICAM-1) and inducing polarization of the microtubule organizing center (MTOC), which leads to formation of the VS (Fukudome et al, 1992; Nejmeddine et al, 2005, 2009). Recent work suggests that next to Tax also HBZ contributes to HTLV-1-infectivity by upregulating ICAM-1 (Fazio et al, 2019). Use of single-cycle replication-dependent HTLV-1 reporter vectors revealed that Tax also enhances actin- and tubulin-dependent transmission of HTLV-1 virus-like particles (Mazurov et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The primary mechanisms for infection via cell-to-cell contact involve the formation of a virological synapse (VS), driven by the polarization of the microtubule organizing center of an infected cell toward a target cell [61,62]. This polarization is triggered by virus-induced upregulation of intercellular adhesion molecule 1 (ICAM-1) on the infected cell and its interaction with lymphocyte function-associated antigen (LFA-1) on the target cell [52,63,64]. The accumulation of Env and other viral proteins, including p19 matrix and p15 nucleocapsid, as well as viral genomes, has been found at this cell-cell interface; therefore, it is thought that viral assembly is coordinated with VS formation and transmission [52,61].…”
Section: Env-mediated Viral Entrymentioning
confidence: 99%